2018
DOI: 10.2147/jaa.s142476
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of fish and shellfish allergies

Abstract: Seafood allergy is a hypersensitive disorder with increasing prevalence worldwide. Effective and accurate diagnostic workup for seafood allergy is essential for clinicians and patients. Parvalbumin and tropomyosin are the most common fish and shellfish allergens, respectively. The diagnosis of seafood allergies is complicated by cross-reactivity among fish allergens and between shellfish allergens and other arthropods. Current clinical diagnosis of seafood allergy is a complex algorithm that includes clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 147 publications
(134 reference statements)
3
37
0
Order By: Relevance
“…This finding again confirmed and proved that tropomyosin is heat resistant in nature and can retain IgE-binding ability even after prolonged heating period (Leung et al, 1998;Motoyama et al, 2007;Kamath et al, 2013). Reese et al (1999) reported that tropomyosin can withstand heat-treatment by most known type of food processing techniques and it could be specifically due to its exceptionally stable alpha helical coiled secondary structure.…”
Section: Immunoblottingsupporting
confidence: 64%
See 1 more Smart Citation
“…This finding again confirmed and proved that tropomyosin is heat resistant in nature and can retain IgE-binding ability even after prolonged heating period (Leung et al, 1998;Motoyama et al, 2007;Kamath et al, 2013). Reese et al (1999) reported that tropomyosin can withstand heat-treatment by most known type of food processing techniques and it could be specifically due to its exceptionally stable alpha helical coiled secondary structure.…”
Section: Immunoblottingsupporting
confidence: 64%
“…Myofibrillar protein, tropomyosin is reported as a major allergen in shellfishes having two identical subunits with molecular weight of 35 to 38 KDa (Shanti et al, 1993;Leung et al, 1998). It is present in both muscle and non-muscle cells.…”
Section: Introductionmentioning
confidence: 99%
“…Their specific implications for risk assessment and cross-reactivities still need to be evaluated, but recent papers support the high predictive value of PAMD@ for risk assessment in patients with fish and shellfish allergies. 220…”
Section: Fishmentioning
confidence: 99%
“…The boy's elder brother response to oyster at the first time when he was 13 years old, which may be a cross-allergic reaction caused by mite allergy. Studies had found that there are cross-reactivities between tropomyosin in molluscs such as oyster and myosin in D.pteronyssinus and D.farinae [7]. This case report has certain limitations.…”
Section: Discussionmentioning
confidence: 82%